2017
DOI: 10.5539/ijbm.v12n11p227
|View full text |Cite
|
Sign up to set email alerts
|

Household Debt and Housing Price: An Empirical Study across 36 Countries

Abstract: This paper investigates the effect of the change of household debt ratio (household debt to GDP) on national housing price by using unbalanced panel data in 36 countries during 1981-2015. We employ Two Stage Least Square and GMM method to analyze the fixed effect model, after controlling the demand, supply, other assets prices and endogeneity. Our findings are that household debt ratio and housing price are positively significantly related. Household debt ratio promotes the growth rate of housing prices. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…So, according to the results of research by F. Lai et al We can see that there is a close direct relationship between such financial indicators as the household debt ratio and the prices of residential real estate objects. At the same time, the growth of the household debt ratio (in national practice -consumer debt) causes a steady trend towards rising prices for housing, its construction, reconstruction, and repair [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, according to the results of research by F. Lai et al We can see that there is a close direct relationship between such financial indicators as the household debt ratio and the prices of residential real estate objects. At the same time, the growth of the household debt ratio (in national practice -consumer debt) causes a steady trend towards rising prices for housing, its construction, reconstruction, and repair [30].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted by F. Lai et al show a close relationship between such financial indicators as household debt rate and housing price. Meanwhile, growing household debt (in domestic practice -consumer debt) generates a steady trend of growing housing, construction, reconstruction, and maintenance prices [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has also shown that certain movements in the economic cycle of certain countries have been caused by the indebtedness promoted by the increase in the price of housing (Illing et al, 2018). According to the International Monetary Fund (IMF), increasing household debt drives economic growth and employment (Lai et al, 2017). Nevertheless, households must slow down spending to pay back their loans, so these effects are reversed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is probably due to the causality between the two variables. Lai et al (2017), studying the effect of a rising household debt on housing prices, argue that the consumer inflation rate must be included among the determinants of house prices.…”
Section: The Effect Of House Price Growthmentioning
confidence: 99%